2019
DOI: 10.1016/j.ekir.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ombitasvir/Paritaprevir/Ritonavir in Patients With Hepatitis C Virus Genotype 1 or 4 Infection and Advanced Kidney Disease

Abstract: IntroductionHepatitis C virus (HCV) infection is common in patients with end-stage renal disease. We investigated the safety and efficacy of ombitasvir (OBV)/paritaprevir (PTV)/ritonavir (r) ± dasabuvir (DSV) ± ribavirin (RBV) in 2 phase 3, open-label, multicenter studies in patients with stage 4 or 5 chronic kidney disease (CKD).MethodsRUBY-I, Cohort 2 enrolled treatment-naïve or -experienced patients with HCV genotype (GT) 1a or 1b infection, with or without cirrhosis. Patients received 12 weeks (24 weeks fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…Concerning the combination paritaprevir/ombitasvir/ ritonavir and dasabuvir, studies have shown good tolerance and efficacy in HCV-infected patients with stage 4/ 5 CKD, including subjects with compensated cirrhosis, previously treated patients and patients undergoing dialysis [10]. We evaluated the safety and efficacy of this therapeutic regimen in a group of 232 patients, including subjects with severe renal impairment, hemodialyzed patients and kidney transplant recipients, all infected with HCV genotype 1.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the combination paritaprevir/ombitasvir/ ritonavir and dasabuvir, studies have shown good tolerance and efficacy in HCV-infected patients with stage 4/ 5 CKD, including subjects with compensated cirrhosis, previously treated patients and patients undergoing dialysis [10]. We evaluated the safety and efficacy of this therapeutic regimen in a group of 232 patients, including subjects with severe renal impairment, hemodialyzed patients and kidney transplant recipients, all infected with HCV genotype 1.…”
Section: Introductionmentioning
confidence: 99%
“…This issue of Kidney International Reports features the results of 2 important studies using DAAs in patients with kidney disease 4, 5. In both studies, the DAA regimen evaluated is paritaprevir with the pharmaco-enhancer ritonavir, ombitasvir, and dasabuvir (PROD), a combination DAA therapy that includes 1 drug from each of the major DAA classes (protease inhibitors, polymerase inhibitors, and NS5A protein inhibitors).…”
mentioning
confidence: 99%
“… 5 Ribavirin (Yes/No)Cure Rate, %Anemia, %aRenal AEs, %All SAEs, %eGFR ≥90 ( n = 1221)Yes964913eGFR 60–89 ( n = 1254)Yes966123eGFR <60 ( n = 59)Yes9378710eGFR ≥90 ( n = 453)No97211eGFR 60–89 ( n = 547)No98221eGFR <60 ( n = 33)No97236 Advanced CKD: Lawitz et al. 4 %Dialysis DAA regimen Duration, wk Cure rate, % Anemia Ruby-I cohortGT1A without cirrhosis ( n = 28)68PROD + ribavirin1296Grade 2–3 in 71%GT1A with cirrhosis ( n = 9)89PROD + ribavirin2489Grade 2–3 in 75%GT1B with or without cirrhosis ( n = 11)73PROD12100Grade 2 in 27%, no grade 3Ruby-II cohortGT1A without cirrhosis ( n = 13)100PROD12100Grade 2 in 31%, no grade 3GT4 without cirrhosis ( n = 5)80PRO1280Grade 2 in 40%, no grade 3AE, adverse event; CKD, chronic kidney disease; DAA, direct-acting antiviral; GT, genotype; PRO, paritaprevir, ritonavir, ombitasvir; PROD, paritaprevir, ritonavir, ombitasvir, and dasabuvir; SAE, serious adverse event.aAnemia defined as hemoglobin decrease to <10 g/dl or ≥2 g/dl from baseline to end of treatment. Unable to determine from text the breakdown of anemia by CKD stage in those treated with regimens that did not include ribavirin; text notes only 2% had comparable hemoglobin reductions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Post hoc analyses of trial data and observational evidence suggest that virologic cure of HCV infection with DAAs improves kidney outcomes (ie, proteinuria and estimated glomerular filtration rate) in many patients with CKD. 12 , 13 , 14 Further investigation with longer follow-up is needed to better understand the effect of DAA treatment on long-term kidney outcomes in patients with CKD, and to evaluate whether treatment reduces adverse outcomes in dialysis patients. 15 In individuals with HCV infection on the kidney transplant waitlist, willingness to accept an HCV-positive donor kidney can greatly reduce the time they wait to receive a kidney transplant.…”
mentioning
confidence: 99%